African Continental Free Trade Agreement (AfCFTA) and Supply Chain Issues in Africa: An Exploratory Review (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The African Continental Free Trade Area (AfCFTA), inaugurated in 2018, represents a pivotal initiative toward regional economic integration, trade liberalization, and sustainable development across Africa. Central to its framework are objectives such as the elimination of trade barriers, a 90% reduction in tariffs, the facilitation of trade in goods and services, and the promotion of economic diversification and industrialization. Despite the official commencement of trading under AfCFTA on January 1, 2021, substantive intra-African trade activities under its provisions remain limited, signaling critical implementation bottlenecks. This study examines the supply chain inefficiencies that hinder the achievement of AfCFTA's objectives and assesses stakeholder perceptions regarding its effectiveness in addressing structural trade challenges. Employing a quantitative research design, primary data were collected through structured surveys administered to stakeholders actively engaged in cross-border supply chain operations within the AfCFTA framework. Findings indicate that persistent infrastructural deficits, non-harmonized trade policies, border inefficiencies, and low levels of technological integration significantly constrain intra-African trade. These challenges have curtailed seamless supply chain operations, undermining the anticipated benefits of the agreement. To address these systemic constraints, the study recommends a multifaceted strategy centered on regional policy harmonization, enhanced public-private collaboration, investment in trade-enabling infrastructure, and the adoption of digital and logistics technologies to foster a resilient and efficient continental supply chain network.